EMPLOYEE PERFORMANCE ANALYSIS REVIEWED FROM THE VARIABLES OF TRANSFORMATIONAL LEADERSHIP STYLE, CAREER ADAPTABILITY, AND JOB SATISFACTION IN JEMBER REGENCY DISPENDIK - Ning Wiyanti, Sekar Bahtera; Winahyu, Pawestri; S, Ira Puspitadewi (Universitas Muhammadiyah Tangerang, 2024)
A person's leadership style in leading is very influential and is a determining factor for increasing and decreasing employee performance, therefore it is clear that every company needs an effective leadership style because in this case it also depends on the reliability and ability of employees in operating work units. existing in an organization, effective leadership and the influence and role of leadership are very necessary because in reality the success of an organization is determined by the leadership and leadership style developed in the organization to achieve the goals of the organization. The purpose of this research is to determine and analyze the influence of transformational leadership style, career adaptability, and job satisfaction on the performance of employees of the Jember Regency Education Office. This type of research is causality research. The population in this study were employees of the Jember Regency Education Office. The sample used was 110 respondents using probability sampling techniques. The analysis tool uses multiple linear regression. The research results prove that transformational leadership style, career adaptability, and job satisfaction have a significant effect on the performance of Jember Regency Education Office employees. It is hoped that the contribution of this research can provide information as a basis for consideration, support and contribution of thought to business decision makers in order to improve company performance.